PENGARUH PRICE EARNING RATIO, PRICE BOOK VALUE DAN EARNING PERSHARE TERHADAP AKTIVITAS VOLUME PERDAGANGAN SAHAM DAN TINGKAT PENGEMBALIAN SAHAM (Studi Pada Saham Indeks Kompas 100 Tahun 2007-2011) - Baiq Retno Sofiana Iqsir; Sapto Hendri BS; Lukman Effendy (Jurnal Riset Akuntansi, 2017)
The objective of this study is to determine the influence of price earnings ratio, price book value and earnings per share on the activity of stock trading volume of companies listed in Kompas 100 Index 2007-2011. This study also aimed to determine the effect of price earnings ratio, price book value and earnings per share on stock returns of companies listed in Kompas 100 Index 2007-2011. Sample was determined based on purposive sampling method which resulted in 31 companies in the Kompas 100 Index stock market index during the years 2007-2011. Hypotheses testing based on multiple linear regression analysis showed that the price earnings ratio (PER), price book value (PBV) and earnings per share (EPS) simultaneously influence the Trading Volume Activity (TVA). However, only Price Book Value (PBV) has partial effect on trading volume. The results also show that price earnings ratio (PER), price book value (PBV) and earnings per share (EPS) has simultaneous influence on stock returns. However, only the variable price book value (PBV) that has partial effect on stock returns.